2018
DOI: 10.1149/2.0101814jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Si Content on the Microstructure and Corrosion Behavior of Additive Manufactured Al-Si Alloys

Abstract: Si10-Mg, and Al-Si12) through a comparative analysis. It explores the influence of the silicon content on the microstructure and corrosion behavior of these alloys. An initial scanning electron microscopy analysis revealed that the silicon content in the samples affected the level of connectivity of the Si network, and this, consequently, influenced the formation of micro-cracks during corrosion. A model describing the evolution of the corrosion attacks and micro-cracks formation in the AM Al-Si alloys is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 32 publications
3
59
0
4
Order By: Relevance
“…This correlated with the coarse structure in the borders that led to the higher driving force for the galvanic corrosion and induced the corrosion attacks along the borders, where the heat-affected zones (HAZ) exhibited broken Si borders (Revilla et al, 2020). The observed corrosion mechanism is in agreement with (Revilla and Graeve, 2018), who reported the initiation of corrosion at the MPB followed by superficial spreading of the corrosion attack to adjacent zones, including the HAZ. The SR process did not notably change the macrostructure of the melting pools, therefore, the form of corrosion attack is similar to that of the untreated as-built samples but with a higher corroded area.…”
Section: Corrosion Mechanismssupporting
confidence: 72%
“…This correlated with the coarse structure in the borders that led to the higher driving force for the galvanic corrosion and induced the corrosion attacks along the borders, where the heat-affected zones (HAZ) exhibited broken Si borders (Revilla et al, 2020). The observed corrosion mechanism is in agreement with (Revilla and Graeve, 2018), who reported the initiation of corrosion at the MPB followed by superficial spreading of the corrosion attack to adjacent zones, including the HAZ. The SR process did not notably change the macrostructure of the melting pools, therefore, the form of corrosion attack is similar to that of the untreated as-built samples but with a higher corroded area.…”
Section: Corrosion Mechanismssupporting
confidence: 72%
“…9. [173][174][175] The potential of the aluminium phase was lower than that of the silicon phase, leading to galvanic corrosion and Fig. 9d displays the intercellular network of silicon in the corroded areas for the SLMed AlSi10Mg alloy in chloride solution.…”
Section: Al-based Alloysmentioning
confidence: 99%
“…The fitting results indicate the polished samples have better corrosion resistance by comparing the value of R ct , but the value of R f for the unpolished samples are larger than the polished samples, it can be inferred that the rougher surface leads to the larger area of the actual surface [86]. The EIS results in the study of Revilla et al revealed that the corrosion resistance is improved with the increasing content of Si [89].…”
Section: Electrochemical Impedance Spectrummentioning
confidence: 95%
“…During the anodic polarizati ve film might form on the electrode surface in a small potential range at which the cu ty remains constant with the growing potential, so the occurrence of the passive film ove the corrosion resistance of matrix [80]. The investigation of Revilla et al suggests tha sion potential is increasing with higher content of Si [89]. hang et al studied the polarization curves of SLM Al-12Si aluminum alloy.…”
Section: 13 X For Peer Review 11mentioning
confidence: 99%